CSAHi study: Detection of drug-induced ion channel/receptor responses, QT prolongation, and arrhythmia using multi-electrode arrays in combination with human induced pluripotent stem cell-derived cardiomyocytes - Kitaguchi, Takashi; Moriyama, Yuta; Taniguchi, Tomohiko; Maeda, Sanae; Ando, Hiroyuki; Uda, Takaaki; Otabe, Koji; Oguchi, Masao; Shimizu, Shigekazu; Saito, Hiroyuki; Toratani, Atsushi; Asayama, Mahoko; et al. (Journal of pharmacological and toxicological methods, 2017)
The use of multi-electrode arrays (MEA) in combination with human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) provides a promising method to predict comprehensive cardiotoxicity, including drug-induced QT prolongation and arrhythmia. We previously demonstrated that MEA in combination with hiPSC-CMs could provide a generalizable platform by using 7 reference drugs at 10 testing facilities. Using this approach, we evaluated responses to reference drugs that modulate a range of cardiac ion currents and have a range of arrhythmogenic effects. We used the MEA system (MED64) and commercially available hiPSC-CMs (iCell cardiomyocytes) to evaluate drug effects on the beat rate, field potential duration (FPD), FPD corrected by Fridericia's formula (FPDc), and the incidence of arrhythmia-like waveforms. This assay detected the repolarization effects of Bay K8644, mibefradil, NS1643, levcromakalim, and ouabain; and the chronotropic effects of isoproterenol, ZD7288, and BaCl2. Chronotropy was also affected by K+ and Ca2+ current modulation. This system detected repolarization delays and the arrhythmogenic effects of quinidine, cisapride, thioridazine, astemizole, bepridil, and pimozide more sensitively than the established guinea pig papillary muscle action potential assay. It also predicted clinical QT prolongation by drugs with multiple ion channel effects (fluoxetine, amiodarone, tolterodine, vanoxerine, alfuzosin, and ranolazine). MEA in combination with hiPSC-CMs may provide a powerful method to detect various cardiac electrophysiological effects, QT prolongation, and arrhythmia during drug discovery. However, the data require careful interpretation to predict chronotropic effects and arrhythmogenic effects of candidate drugs with multiple ion channel effects.